Mechanical Properties of A356 Matrix Composites Reinforced with Nano-SiC Particles - Mazahery, A.; Shahani, M.O. (Проблемы прочности, 2012)
Metal matrix composites form one group of the new engineered materials in which a strong ceramic reinforcement is incorporated into a metal matrix to improve its properties including specific strength, specific stiffness, wear resistance, excellent corrosion resistance and high elastic modulus. A compocasting method was employed to incorporate SiC nano-particles into the aluminum alloy and fabricate metal matrix nanocomposites with uniform reinforcement distribution. Microstructural characterization of compocast composites show a uniform distribution of nano-particles, grain refinement of aluminum matrix, and presence of the minimal porosity. It was revealed that the presence of nano-SiC reinforcement led to significant improvement in hardness, 0.2% yield strength and UTS while the ductility of the aluminum matrix is retained. Композиты с металлической матрицей образуют группу новых искусственно спроектированных материалов, в металлическую матрицу которых вводятся керамические упрочняющие компоненты с целью улучшения ее механических свойств, включая удельную прочность и удельную жесткость, а также износостойкость, и обеспечения высокой коррозионной устойчивости и высокого модуля упругости. Метод композиционного литья использовался для введения наночастиц SiC в алюминиевый сплав и изготовления нанокомпозитов с металлической матрицей и однородным распределением упрочняющих компонентов. Микроструктурный анализ композитов, полученных методом композиционного литья, показал однородное распределение наночастиц, уменьшение размеров зерен матрицы из алюминиевого сплава и минимальную пористость материала. Установлено, что наличие наночастиц карбида кремния существенно повышает твердость, условный предел текучести и предел прочности при сохранении исходной пластичности алюминиевой матрицы. Композити з металічною матрицею утворюють групу нових штучно спроектованих матеріалів, у металічну матрицю яких вводяться керамічні зміцнювальні компоненти з метою покращання її механічних властивостей, включаючи питомі міцність і жорсткість, а також зносостійкість, та забезпечення високої корозійної стійкості і високого модуля пружності. Метод композиційного лиття використовувався для введення наночастинок SiC у алюмінієвий сплав та виготовлення нанокомпозитів із металічною матрицею й однорідним розподілом зміцнюваних компонентів. Мікроструктурний аналіз композит ів, що отримані методом композиційною лиття, показав однорідний розподіл наночастинок, зменшення розмірів зерен матриці з алюмінієвого сплаву та мінімальну пористість матеріалу. Установлено, що наявність наночастинок карбіду кремнію суттєво підвищує твердість, умовну границю текучості і границю міцності при збереженні початкової пластичності алюмінієвої матриці.